Characterization and mutagenesis of Chinese hamster ovary cells endogenous retroviruses to inactivate viral particle release. Issue 2 (12th November 2019) - Duroy, Pierre‐Olivier; Bosshard, Sandra; Schmid‐Siegert, Emanuel; Neuenschwander, Samuel; Arib, Ghislaine; Lemercier, Philippe; Masternak, Jacqueline; Roesch, Lucien; Buron, Flavien; Girod, Pierre‐Alain; Xenarios, Ioannis; Mermod, Nicolas
Abstract: The Chinese hamster ovary (CHO) cells used to produce biopharmaceutical proteins are known to contain type‐C endogenous retrovirus (ERV) sequences in their genome and to release retroviral‐like particles. Although evidence for their infectivity is missing, this has raised safety concerns. As the genomic origin of these particles remained unclear, we characterized type‐C ERV elements at the genome, transcriptome, and viral particle RNA levels. We identified 173 type‐C ERV sequences clustering into three functionally conserved groups. Transcripts from one type‐C ERV group were full‐length, with intact open reading frames, and cognate viral genome RNA was loaded into retroviral‐like particles, suggesting that this ERV group may produce functional viruses. CRISPR‐Cas9 genome editing was used to disrupt the gag gene of the expressed type‐C ERV group. Comparison of CRISPR‐derived mutations at the DNA and RNA level led to the identification of a single ERV as the main source of the release of RNA‐loaded viral particles. Clones bearing a Gag loss‐of‐function mutation in this ERV showed a reduction of RNA‐containing viral particle release down to detection limits, without compromising cell growth or therapeutic protein production. Overall, our study provides a strategy to mitigate potential viral particle contaminations resulting from ERVs during biopharmaceutical manufacturing. Abstract : Endogenous retroviruses in Chinese hamster ovary cells were characterized at the genome, transcriptome and viral particle level. Following CRISPR‐mediated mutagenesis, the authors identified a single endogenous retrovirus locus responsible for the budding of viral particles into the cell supernatant. Loss‐of‐function mutations in this particular locus reduced viral genome‐containing viral particles to detection limits, thus augmenting the safety profile of Chinese hamster ovary cells for biopharmaceutical production.